Digitalization Of Banking Services In Algeria - Bouaichi ,Numidia; Bennacer ,Nasreddine (University of Eloued جامعة الوادي, 2025)
Like all countries, Algeria began digitizing its banking services in the 1990s. The goal is to facilitate and make them accessible while ensuring their security, and to align with international economic transformations. This study focuses on digital banking services in Algeria. It aims to identify their emergence, assess the extent to which they are used by customers, and analyze the barriers and obstacles to their widespread adoption. To this end, we conducted a field survey by distributing a questionnaire to bank customers. Initial results demonstrate a certain transition toward digitization, as digital banking services are increasingly used, particularly in payment transactions. However, several barriers and obstacles hinder their widespread adoption (customer reluctance, unstable connection, etc.).
مقال
Keywords: Digitization; digital banking service; Algerian bank; e-payment; field survey